Penerapan Standar Operasional Prosedur Pada Klinik Utama Vincentius Kristus Raja Surabaya - Jeanne Asteria Wawolangi; Anita Permatasari (BIP's JURNAL BISNIS PERSPEKTIF, 2021)
Vincentius Kristus Raja (KR) Main Clinic aims to serve patients effectively and economically in an effort to improve the quality of public health services, especially in Surabaya. This type of research is descriptive qualitative in the form of a case study, to assess the implementation of standard operating procedures at the Vincentius Kristus Raja Main Clinic. Relevant data collection was carried out using questionnaires distributed to personnel related to standard operating procedures. The results of the research study according to the questionnaire indicate that the operational implementation is in accordance with the standard operating procedures that have been set based on the policies of the leadership and the Vincentius Kristus Raja Main Clinic Foundation. Compliance with standard operating procedures is very important because standard operating procedures are guidelines or references for carrying out tasks and work in accordance with their functions. The conclusions and suggestions from this study are that although compliance with standard operating procedures is adequate, the Vincentius Kristus Raja Main Clinic needs to develop and improve the quality of services, especially better communication with patients, both new patients and patients who have been on treatment for a long time at the Vincentius Kristus Raja Main Clinic. Considering that there are now many new health clinics that can be competitors for the Vincentius Kristus Raja Main Clinic, there must be a good response to this phenomenon. The emergence of these new competitors requires the Vincentius Kristus Raja Main Clinic to be able to be competitive in order to face the existing competition by improving the quality and quality of service for patients.